THE NEEDS OF LANGUAGE ASSESSMENT TO FOSTER STUDENT LEARNING OF ENGLISH AS A SECOND LANGUAGE - Safitri, Nyimas Triyana (Universitas Jambi, 2014)
The assessment of studentsâ skills of ESL has become a fundamental aspect of teaching and learning language at schools level. It can be seen as the process of collecting the information about students to help language teachers in decision making about studentsâ progress and language development. In ESL instructional context, assessment practice essentially focuses on the process of making efforts and contributions for students to improve language learning outcomes. To achieve this goal, it is expected that language teachers should have literacy in assessment concepts, knowledge or skills and strategies to assist students to achieve the higher level of language learning performance and achievement. This is also an essential aspect of developing studentsâ language competences in relation to acquire and learn English as a second language that involves the way language teachers evaluate studentsâ performance in learning ESL andÂ language aspects that needed to be assessed. Hence, ESL assessment practice should be implemented as a continous evaluation in assisting language teacher to provide students with a better understanding on language learning.